A "Rapid Best‐Fit" model for framework synthesis: Using research objectives to structure analysis within a rapid review of qualitative evidence. (20th October 2020) - Shaw, Liz; Nunns, Michael; Briscoe, Simon; Anderson, Rob; Thompson Coon, Jo
Abstract : The short time frame associated with rapid reviews can be challenging for researchers conducting qualitative evidence synthesis. In these circumstances a Best‐Fit Framework Synthesis, drawing upon existing theory and/or research, may be conducted to rapidly make sense of qualitative evidence. This article discusses a "Rapid Best‐Fit" approach to conducting Framework Synthesis within an 6‐week rapid systematic review of qualitative evidence. In the absence of a suitable theoretical model to inform the synthesis, we drew upon our research objectives to structure a framework, and to identify the studies which contained the most relevant data. Themes from these studies were used to revise the initial framework before inductive thematic synthesis finalized theme content. This "Rapid Best‐Fit" approach yielded results aligned with the needs of the commissioners of the review and is a useful addition to qualitative synthesis methods, allowing for the incorporation of diverse views and experiences into fast‐paced decision making scenarios.